The Evaluation of Cardiovascular System Before and After Renal Transplantation and Its Relationship Between Brain Natriuretic Peptide - Ayşe Fıtnat Tuncel Bahar; Hatice Paşaoğlu; Ayşe Deniz Oğuz; Sevcan Bakkaloğlu; Enver Hasanoğlu; Banu Kadıoğlu Yılmaz (Genel Tıp Dergisi)
Aim: To evaluate the cardiovascular system functions biochemically and echocardiographically in renal transplant recipients before and after transplantation. Materials and Methods: Patients who were followed up in Gazi University Faculty of Medicine, Department of Pediatric Nephrology and diagnosed with CRF, and underwent renal transplantation before the age of 18 were included in the study. A control group was formed from healthy volunteers. BMI, biochemical values, echocardiographic findings, and CIMT measurements of these patients before and after transplantation were compared. Tissue Doppler imaging and BNP values performed after transplantation were compared with the control group. Results: Data from 64 subjects (patient group;32, healthy control group;32) were evaluated. Values of the patients before and after renal transplantation were compared. BMI values increased significantly after transplantation compared to pre-transplantation (p